THE CORELATIONS BETWEEN WHITE ROT (RIGIDOPORUS LIGNOSUS L.) INCIDENCE AND SOIL CHARACTERS OF RUBBER ECOSYSTEM IN PENUMANGAN BARU, LAMPUNG - Joko Prasetyo, Titik Nur Aeny,; Radix Suharjo . (Universitas Lampung, 2009)
The corelations between White Rot (Rigidoporus lignosus L.) incidence and soil characters of rubber ecosystem in Penumangan Baru, Lampung. A study was conducted to evaluate the corelation between soil characters and white rot incidence. The study was done in Penumangan Lampung from June 2007 to July 2008. Seven sites were observed on the incidence of white rot of indicator plants (cassava). Physical, chemical, and biological soil characters were correlated and regressed with white rot incidence. The results showed that there were correlation between white rot incidence and soil characters such as pH KCl, number of fungal genus (fungal diversity), Ca+, total cation, CEC, and saturation base. Ion Ca+, total cation, saturation base correlated positively with white rot incidence, on the contrary, fungal diversity, cation exchange capacity, and pH KCl correlated negatively with white rot incidence. Thus, efforts to increase fungal diversity, cation exchange capacity, and pH (in acidic soil) could be used as basic strategies to develope intergrated control of white rot disease.